Periodontal Pathogens: A Crucial Link Between Periodontal Diseases and Oral Cancer - Li, Tian-Jiao; Hao, Yi-hang; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Microbiology, 2022)
Emerging evidence shows a striking link between periodontal diseases and various human cancers including oral cancer. And periodontal pathogens, leading to periodontal diseases development, may serve as a crucial role in oral cancer. This review elucidated the molecular mechanisms of periodontal pathogens in oral cancer. The pathogens directly engage in its own unique molecular dialogue with the host epithelium to acquire cancer phenotypes, and indirectly induce proinflammatory environment and carcinogenic substance in favor of cancer development. And functional, rather than compositional, properties of oral microbial community correlated with cancer development are discussed. The effect of periodontal pathogens in periodontal diseases and oral cancer will further detail the pathogenesis of oral cancer and intensify the need of maintaining oral hygiene for prevention of oral diseases including oral cancer.